To work or not to work: Variables affecting non‐financial employment commitment over time. (10th July 2019) - SHARABI, Moshe; HARPAZ, Itzhak
Abstract: The most common indicator of non‐financial employment commitment (NFEC) is the "lottery question" – whether a person would continue working if they won a lottery. This cross‐sectional research seeks to identify the demographic variables and the "meaning of work" dimensions that could predict individual NFEC, presenting the main international findings over time, with particular reference to data collected in Israel in 1981, 1994 and 2006. The authors' findings point to a marked decrease in NFEC in the new millennium and a change in its predictors over time. The findings and their implications for work and employment are examined in the light of social and economic changes in Israel.